2015
DOI: 10.1038/nm.3824
|View full text |Cite
|
Sign up to set email alerts
|

Brain somatic mutations in MTOR cause focal cortical dysplasia type II leading to intractable epilepsy

Abstract: Focal cortical dysplasia type II (FCDII) is a sporadic developmental malformation of the cerebral cortex characterized by dysmorphic neurons, dyslamination and medically refractory epilepsy. It has been hypothesized that FCD is caused by somatic mutations in affected regions. Here, we used deep whole-exome sequencing (read depth, 412-668×) validated by site-specific amplicon sequencing (100-347,499×) in paired brain-blood DNA from four subjects with FCDII and uncovered a de novo brain somatic mutation, mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
413
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 446 publications
(464 citation statements)
references
References 38 publications
21
413
0
8
Order By: Relevance
“…These findings also suggest that hyperactivated mTOR kinase is a therapeutic and genetically validated target in individuals with FCD. 8 Although the genetic etiology and molecular pathogenesis of FCD remain to be fully defined, our study has not only revealed additional somatic mosaic mutations that lead to FCD but also described the generation of a mouse model with brain somatic mutations via in utero somatic genome-editing technology. This study will provide a foundation for future clinical and scientific research of FCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings also suggest that hyperactivated mTOR kinase is a therapeutic and genetically validated target in individuals with FCD. 8 Although the genetic etiology and molecular pathogenesis of FCD remain to be fully defined, our study has not only revealed additional somatic mosaic mutations that lead to FCD but also described the generation of a mouse model with brain somatic mutations via in utero somatic genome-editing technology. This study will provide a foundation for future clinical and scientific research of FCD.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize erroneous and false-positive mutations that could mimic low-level somatic mutations, we performed cross-platform replications by adopting both hybrid capture and PCRbased amplicon sequencing of five genes. 8,39,40 To detect true de novo somatic mutations, we selected overlapping mutations in both sequencing platforms and then performed simple filtering steps ( Figure S2). The subjects were considered to have a mutation when the percentage of mutated reads exceeded 103 (1%) the expected base miscall rate (0.1%).…”
Section: In Vivo Rapamycin Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…TSC is naturally a mutation of either TSC1 or TSC2 in 85%, whereas more than half of those cases show also mosaicism 43. Recent studies found somatic (mosaic) mutations affecting the mTOR signaling also in focal lesions of FCD II patients 4, 8, 21, 25, 32, 36. This is a very important aspect since as far as we know, in FCD, the mutations are localized and show profound variability in cellular expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent literature points to the involvement of the mTOR pathway in FCD type II,9, 10, 11, 12 the exact molecular mechanism leading to this type of cortical malformation, especially to the presence of aberrant cells, remains undetermined 13, 14. As the development of the cerebral cortex is a sophisticated process, requiring the fine‐tuning of gene expression, we decided to analyze the expression of microRNAs as a shortcut to gain a better understanding of the mechanisms involved in the pathogenesis of FCD type II.…”
mentioning
confidence: 99%